Association between COMT Val158Met and DAT1 polymorphisms and depressive symptoms in the obese population - Bieliński M (Dove Medical Press, 2017)
Maciej Bieliński,1 Marcin Jaracz,1 Natalia Lesiewska,1 Marta Tomaszewska,1 Marcin Sikora,2 Roman Junik,3 Anna Kamińska,3 Andrzej Tretyn,2 Alina Borkowska1 1Department of Clinical Neuropsychology, Nicolaus Copernicus University in Toruń, Collegium Medicum in Bydgoszcz, Bydgoszcz, 2Department of Biotechnology, Nicolaus Copernicus University in Toruń, Toruń, 3Department of Endocrinology and Diabetology, Nicolaus Copernicus University in Toruń, Collegium Medicum in Bydgoszcz, Bydgoszcz, Poland Objectives: Depressive symptoms are common among patients with obesity. Abnormalities in dopamine signaling involved in the reward circuit may ensue excessive consumption of food, resulting in obesity and leading to neuropsychiatric disorders such as depression. This study sought to investigate the association of polymorphisms in the genes encoding DAT1/SLC6A3 and COMT with the intensity of depressive symptoms in obese subjects.Participants and methods: Prevalence and severity of depressive symptoms were assessed in a group of 364 obese patients using the Beck Depression Inventory (BDI) and the Hamilton Depression Rating Scale (HDRS). Genetic polymorphisms in DAT1 and COMT were evaluated in peripheral blood samples.Results: The results indicated an association between DAT1 alleles and depressive symptoms, as well as severity of obesity. Subjects homozygous for the nine-repeat allele scored higher in BDI (P=0.022) and HDRS (P=0.00001), suggesting higher intensity of depression in both sexes. This allele was also associated with the highest body mass index (BMI; P=0.001). Carriers of the Val158Met allele of COMT scored higher on both depression scales (BDI, P=0.0005; HRDS, P=0.002) and had the highest BMI values.Conclusion: Polymorphisms in the DAT1 and COMT genes are associated with a greater intensity of depressive symptoms in the obese population.Keywords: dopaminergic signaling, obesity, depressive symptoms, reward circuit, gene polymorphism